Effects of nitrogen treatment and intra-row spacing on the morphological and physiological characteristics in pumpkin (Cucurbita pepo L.) - Nastran HAMIDI; Hamid MOHAMMADI; Lamia VOJOUDI; Amirreza SADEGHI (Acta Agriculturae Slovenica)
Pumpkin (Cucurbita pepo L.) is a medicinal plant recently under common cultivation in Iran. The seeds and its products are used in the treatment of some diseases. Due to the lack of information about the intra-row spacing and nutritional demands of the plant a factorial experiment with Randomized Complete Block Design with three replications was planned in Azarbaijan Shahid Madani University Research Field in 2013. The treatments were 5 levels of Urea fertilizer (0, 50, 100, 150, 200 kg/ha nitrogen), and intra-row spacing in 3 levels (30, 60 and 90 cm). The result showed that interaction effects of intra-row spacing and nitrogen treatment had significant effect on some morphological traits such as plant height, number of auxiliary branches and leaf number per plant. Application of 200 kg/ha nitrogen increased the plant height, the number for auxiliary branches and leaves as well as the leaves dry mass, mainly due to the prolonged vegetative growth period and delayed flowering and fruiting. 150 kg/ha nitrogen combined with 60 cm intra-row spacing hold the highest number of female flowers, fruit number and intact fruit number and fruit fresh weight, and the highest dry weight of the intact seeds. The results for some physiological traits showed that interaction effects of nitrogen and intra-row spacing had significant effects on chlorophyll b at the late stages of flowering period and the contents for chlorophyll a and carotenoids were significant at the end of growing season. The highest oil content was recorded in 150 kg/ha nitrogen and 60 cm intra-row spacing. Based on results obtained, 150 kg/ha nitrogen and 60 cm intra-row spacing were the best regime for the production of this plant.